Método de costos por órdenes de producción y la incidencia en la rentabilidad de la empresa Santa María de Limache, dedicada al cultivo de brócoli, cantón Latacunga, provincia de Cotopaxi - Caisaguano Chango, Vanessa Yajaira (2017)
In the present investigation, the analysis of the system of costs by orders of production and the incidence in the profitability of the company producing broccoli, was carried out through the compilation of bibliographical information, application of techniques and research instruments such as direct observation, the survey And the elaboration of a simulation with the system of costs by processes; Obtaining as a result of the simulation that there is a difference between the unit production costs of both systems of 0.01 ctv. Because in the company's production schedule it was proposed to add 10% more to the production, in which it was found that the company to obtain a favorable cost of production unit has a profit in relation to the sales price, such Form this profit allows the company to recover its initial investment, on the other hand the existence of punishments and discounts for not delivering production in time causes a decrease in sales volume and an impairment to its profitability, the application of profitability indicators Allowed to know the real situation of the company, nevertheless in making this comparison under the simulation and the current system it was found that there is a minimum difference between both systems, so it is concluded that a cost system if it affects the profitability of the company . The results obtained will be used as a means of consultation for the other companies dedicated to the cultivation of broccoli that is found around the sector, since this research will allow the other industrialists of this product to verify if they are making a correct allocation of costs in terms of the production of the broccoli crop.